KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMODERASI PENGARUH PERENCANAAN PAJAK PADA NILAI PERUSAHAAN - Kusumayani, Happy Apsari; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
Knowing that tax planning an affect firm value that listed at manufacturing companies  on period 2011 - 2014 with moderating variable that is managerial ownership and institutional ownership is the aims of this research. Total sample of this research has 80 observati that choosen by applying non probability method and purposive sampling technique. L inear regression and Moderated Regression Analysis (MRA) can used in analyzing the data in this research . Based of the result of a second analysis founded so that the conclusion of this research that is : 1)  tax planning has a negative influence on firm value of manufacturing; 2) managerial ownership is able to weaken the negative influence of tax planning on firm value of manufacturing; and 3) institutional ownership unable to moderated the influence of tax planning on firm value of manufacturing.
Keywords: Manufacturing, firm value, tax planning, managerial ownership, institutional ownership